Complex Hydrides for Electrochemical Energy Storage. (9th January 2014) - Unemoto, Atsushi; Matsuo, Motoaki; Orimo, Shin‐ichi
<x xml:space="preserve">Abstract</x> Complex hydrides have energy storage‐related functions such as i) solid‐state hydrogen storage, ii) electrochemical Li storage, and iii) fast Li‐ and Na‐ionic conductions. Here, recent progress on the development of fast Li‐ionic conductors based on the complex hydrides is reported. The validity of using them as electrolytes in all‐solid‐state lithium rechargeable batteries is also examined. Not only coated oxides but also bare sulfides are found to be applicable as positive electrode active materials. Results related to fast Na‐ionic conductivity in the complex hydrides are presented. In the last section, the future prospects for battery assemblies with high‐energy densities, and Mg ion batteries with the liquid and the solid‐state electrolytes are discussed.